Solving a multimodal transport problem by DCA - Le Thi, Hoai An; Ndiaye, Babacar Mbaye; Pham Dinh, Tao (2008 IEEE International Conference on Research, Innovation and Vision for the Future Information and Communications Technologies, 2008)
The combined transport appears as a promising alternative to road transportation for containers allocation. It possesses a strong potential market, conditioned by the development of its quality of service (improvement of the system, terminals, and service performances in terminals). Multimodal transport of containers can be an alternative to the road transportation but it requires to be competitive in term of quality of service and price.